Peningkatan Keterampilan Passing Bawah Bola Voli Dengan Metode Berpasangan - AJi Suryo Putro, Waskito; Gegetu, Arbaya; Retno Widiyaningsih, Wahyu; Bumburo, Bandung (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Improving underhand passing skills with the pairing method of the Unimuda volleyball team in Sorong Regency. In volleyball, underhand passing is an important basic technique, because underhand passing is the first touch and the key to success in carrying out an attack, but there are still many mistakes made when doing underhand passing. This is due to the lack of training to improve underhand passing skills, especially for players who feel bored when given continuous training so that it has an impact on less than optimal training. Therefore, a study was conducted with the aim of improving underhand passing skills with the pairing method. With a playing approach. This study uses an experimental method with a one group pretest and posttest design. In this study, a sample of 20 people was taken from the Unimuda volleyball team. Brady volleyball test was then carried out data processing using normality tests, sample t-tests. Research on improving underhand passing skills in volleyball games and has an influence of 71.4%.